2007
DOI: 10.1111/j.1365-2672.2007.03392.x
|View full text |Cite
|
Sign up to set email alerts
|

Redox potential to discriminate among species of lactic acid bacteria

Abstract: Aims:  To verify to what degree reducing capacity is a characterizing parameter of a species, and of the strains themselves within a given species, of lactic acid bacteria. Methods and Results:  Eighty‐eight strains belonging to 10 species of lactic acid bacteria (LAB) isolated from traditional Italian cheeses were studied for their reduction activity: Enterococcus faecalis, Enterococcus faecium, Enterococcus durans, Streptococcus thermophilus, Lactococcus lactis ssp. lactis, Lactobacillus paracasei ssp. parac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
58
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(65 citation statements)
references
References 21 publications
6
58
0
1
Order By: Relevance
“…This corroborates redox development described for other bacterial species (e.g. Brasca et al 2007;Reichart et al 2007;Tachon et al 2010). At the onset of the stationary growth phase, redox potential measurements became more variable.…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…This corroborates redox development described for other bacterial species (e.g. Brasca et al 2007;Reichart et al 2007;Tachon et al 2010). At the onset of the stationary growth phase, redox potential measurements became more variable.…”
Section: Discussionsupporting
confidence: 73%
“…The redox measurements were similar in both liquid cultures and mono-specific sediment microcosms, although sediment microcosm appeared more variable among replicates compared to liquid cultures. However, the reported variations correspond well with species-specific E h variations as described previously (Brasca et al 2007). Subsequent addition of formalin in order to stop bacterial metabolism at the progressive stage of bacterial growth reduced variability in E h measurements (Fig 1a-c, right panel).…”
Section: Monospecific Cultures and Microcosmssupporting
confidence: 74%
See 1 more Smart Citation
“…Some studies showed that it plays an important role in many biological media such as milk-based products (Brasca et al, 2007), wine (Tomlinson and Kilmartin, 1997) and the rumen (Marounek et al, 1982;Marden et al, 2008), where E h is a major factor determining the type of microorganisms that will grow in the milieu (Brasca et al, 2007). Because of the continuous fermentative processes in the rumen involving different simultaneous chemical reactions, it seems interesting to focus on E h in such a reducing environment.…”
Section: Introductionmentioning
confidence: 99%
“…The reason was the interaction between the starter bacteria. Streptococci lowered the redox potential (Brasca et al 2007), which supported the growth of bifibobacteria (Bolbuc et al 2006) and lactobacilli. On the contrary, lactobacilli released amino acids from milk proteins (Lane & Fox 1996) which stimulated the growth of streptococci (Ashraf & Shah 2011) and bifidobacteria (Bolbuc et al 2006).…”
Section: Resultsmentioning
confidence: 99%